Wetland ecology principles and conservation - Keddy, Paul A (Cambridge University Press / Cambridge, 2000)
Contents: Wetland an averview; zonation and succession herbivory; Burial; Wetland restoration assembly roles in the service of conservation; A functional approach; Wetland conservation management and research